TINGKAT URBANSASI DI KOTA PADANG TAHUN 2010, 2015 DAN 2020 - Ilham Rahmat Yadi; Yurni Suasti (JURNAL BUANA, 2022)
Abstract Urbanization is one of the indicators in population growth, population growth in Indonesia is still relatively high.In 2010 the city of Padang had a population of 836,671 people with a population density of 1,260 percent.The city of Padang has undergone the process of urbanization. This study aims to (1) describe the level of urbanization in each district of padang city, (2) describe the level of urbanization of the city of Padang.The method in this study used Secondary Data Analysis (ADS). The findings of the study, the level of urbanization in each sub-district in the city of Padang is included in the low criteria because it is below 22.22%, while for the city of Padang as a whole is included in the criteria that is being between 22.22%-55,55%.